Inovasi Media Pembelajaran Berbasis ICT terhadap Kecerdasan Visual Peserta Didik dalam Pendidikan Agama Islam - Moh. Sutomo; Moh. Sahlan; Afifah Zahro' (STAI Terpadu Yogyakarta, 2022)
This Research Method is using library research. Collecting data that used is text and discourse analysis's. Text and discourse which is meant is from many articles and books related to ICT based learning media innovation against visual intelligence in Islamic religion studied. This research describe ICT based learning media, visual intelligence, Islamic religious education, and ICT based learning media innovation against visual intelligence in Islamic religious education. Use of learning media against student first, educator must know students characteristics, including the students that has visual intelligence. The Educator must adapt that student learning style that tend to refer to the intelligence that students have. Educator can apply learning media by entering the world of students. ICT-based learning media that Islamic religious education educators can use for students who have visual intelligence in learning are digital slideshows, mindmaps, and videos. Educators can utilize Microsoft Powerpoint and Lectora Inspire which can present abstract material to become more concretely in front of students, such as text that represented by images on the slides. Educators can utilize mindmaps in presenting material. Mindmaps can be used because students like designs and mind maps that are accessible to students, so that the material can be accepted by students. Educator can utilize video in presenting moving images that are able to present actual objects with the original layout of the object as well as duplicating actual objects, such as learning animation videos.